Ecoregional research at ILRI: background - Li Pun, H.H.; Jabbar, M.A.; Thornton, Philip K. (International Livestock Research Institute, 1999)
This paper looks briefly at ecoregional research: what is commonly meant by the term and how it may be carried out. ILRI's involvement in various ecoregional consortia is discussed, together with problems and constraints that have been faced to date. The paper ends by listing a number of issues that require resolution if substantive progress is to be made in ecoregional research at ILRI and if the potential benefits of small teams of scientists located in different regions are to be realised. The objective of the workshop is to work towards solving some of these issues, by sharpening both focus and methods of ecoregional research at ILRI.